Carbon emission and energy risk management in mega sporting events: challenges, strategies, and pathways - Su, Xiao-zhong; Chen, Li; Xu, Xin Long (Frontiers in Environmental Science, 2025)
Carbon emissions from mega sporting events pose a serious challenge to the sustainable development of the global environment, and the management of carbon emissions and energy efficiency in sporting events has become a focus of attention for both countries and international organizations. However, most existing research focuses on carbon emissions in sporting events is limited by a narrow focus on individual cases, limited attention to indirect emissions, insufficient integration of socioeconomic dimensions, a lack of broader data coverage, the adoption of interdisciplinary methodologies, and an emphasis on lifecycle energy risk management to provide robust support for sustainable event practices and policy development. To remedy these deficiencies, this study systematically compiles the current situation of carbon emissions in sports activities, analyzes the carbon emission characteristics and energy-saving potential of different types of sporting events, and summarizes the excellent cases of carbon emission and energy efficiency management in sports activities. The study reveals that large-scale sporting events generate substantial carbon emissions and energy consumption in transportation, venue construction, and event operation. However, carbon emissions and energy usage can be significantly reduced by optimizing venue locations, promoting green transportation, and implementing energy-saving measures at all stages. This study not only provides empirical data and theoretical support for the management of carbon emissions and energy efficiency in sporting events but also proposes practical and feasible suggestions that are highly important for the sustainable development of future sporting events. The findings have reference value for policymakers and event organizers in planning and implementing energy-saving and low-carbon events, helping promote environmental governance and sustainable development in the sports sector.